Animation Technique and Depiction of Death in Sculptural Art: Ramayana Story in Shri Ramaswamy Temple in Erstwhile Travancore, Kerala - Preeta Nayar
Artists have, on rare occasions, employed animation techniques in sculptural art to represent movement in time. Ramayana story narrated in wood in Shri Ramaswamy temple has used this technique while presenting the death of Tataka, Subahu, Maricha and Jatayu. Sculptors created twin images of the busts and heads of these characters and conjugated them on their main bodies to represent the sequence of their death. This technique helps sculptors to use minimum space with maximum effect and infuse life in to still images.